Antagonistic Antibody Targeting TNFR2 Inhibits Regulatory T Cell Function to Promote Anti-Tumor Activity - Chen, Yonglin; Jia, Manxue; Wang, Sharon; Xu, Sherry; He, Nanhai (Frontiers in Immunology, 2022)
Infiltration of Regulatory T cells (Tregs) in the tumor microenvironment suppresses anti-tumor immune response, and promotes tumor progression. Tumor necrosis factor receptor‐2 (TNFR2), which is highly expressed on Tregs, activates Tregs through nuclear factor kappa B (NF-κB) pathway. Moreover, TNFR2+ Tregs have been shown to be most suppressive among all Tregs populations in tumor. Due to the unique expression pattern and function of TNFR2 on Tregs, a TNFR2 blocking antibody is expected to compromise Tregs function, relieve Tregs-mediated immunosuppression, and hence to enhance anti-tumor immune response. AN3025 is an antagonistic anti-human TNFR2 antibody that is currently under preclinical development. This study investigates the immunomodulatory and anti-tumor activity of AN3025. AN3025 was generated through rabbit immunization with extracellular domain of human TNFR2 (hTNFR2) and subsequent humanization by CDRs grafting. AN3025 binds to the extracellular domain of both human and cynomolgus with sub-nanomolar affinity and specificity, but not mouse or rat TNFR2. AN3025 inhibited TNFα induced cell death of hTNFR2-overexpressing Jurkat cells by competing with TNFα for binding to hTNFR2. In the Tregs/T effector co-culture assay, AN3025 increased T effector proliferation and enhanced IFNγ production. As a monotherapy, AN3025 significantly inhibited MC38 tumor growth in TNFR2 humanized mouse model. Subsequent FACS and IHC and analysis revealed that administration of AN3025 led to decreased Tregs population, increased CD4+ and CD8+ T cell numbers in the tumor. The anti-tumor activity of AN3025 was dependent on the existence of CD4+ and CD8+ T cells, as depletion of CD4+ and CD8+ T cells abolished the anti-tumor activity of AN3025. In addition, AN3025 in combination with anti-PD-1 antibody demonstrated stronger in-vivo anti-tumor activity. The potent anti-tumor efficacy of AN3025, either as a monotherapy or in combination with anti-PD-1 antibody, supports its further clinical development for the treatment of various human tumors.